Illicit Enrichment in Corruption Eradication in Indonesia: A Future Strategy - Yusuf, M.; Aswanto, Aswanto; Sumardi, Juajir; Maskun, Maskun; Ab Rahman, Nurul Hidayat (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
Corruption crimes in Indonesia are on the rise, particularly through illicit enrichment where individuals accumulate wealth outside of legitimate income. Although Indonesia has ratified the United Nations Convention Against Corruption (UNCAC), the specific issue of illicit enrichment outlined in Article 20 has yet to be implemented in national legislation. This article aims to investigate current and potential future strategies to combat such corruption. The research is a normative study using a comparative law approach and corpus-based critical analysis to assess Indonesia's anti-corruption efforts, explore the international standards set by illicit enrichment regulations, and draw lessons from the unexplained wealth laws in the United Kingdom and Australia. This research concludes that Indonesia has ratified UNCAC, but illicit enrichment in Article 20 of UNCAC has not been regulated in the law, so the practice of corruption is still so massive. To overcome this, strategic steps are needed in the future, such as revising the corruption law to include illicit enrichment regulations, optimizing institutions through bureaucratic reform, and activating community participation. Therefore, these three steps are very important in implementing the Illicit Enrichment regulation in advancing the corruption eradication agenda in Indonesia in the future.